Association of IS605 and cag-PAI of Helicobacter pylori Isolated from Patients with Gastrointestinal Diseases in Taiwan. (17th February 2013) - Lai, Chih-Ho; Perng, Chin-Lin; Lan, Keng-Hsin; Lin, Hwai-Jeng
Abstract : Background . The cag pathogenicity island ( cag -PAI) is one of the most important virulent determinants of Helicobacter pylori . An insertion sequence (IS) element of cag -PAI (IS605) has been found to generate H. pylori strains with varying virulence. Aim . To evaluate the impact of IS605 and cag -PAI on H. pylori strains isolated from Taiwanese patients with severity of gastric diseases. Methods . H. pylori isolates were cultured from gastric biopsies from 99 patients with peptic ulcer, chronic gastritis, and gastric carcinoma. Six distinct, well-separated colonies were isolated from each patient and analyzed by genotyping. Results . cagA, cagE, cagM, cagT, orf 10, and orf 13 were found to be present in 90.0%–100.0% of the H. pylori isolates. A total deletion of cagA, cagE, cagM, cagT, orf 10, and orf 13 was found in 1 isolate (1.0%). The IS605 element was found to be positive in 15.2% of the isolates. The presence of IS605 was higher in H. pylori isolated from patients with gastric carcinoma (25.0%) than in patients with duodenal ulcer (6.5%) or chronic gastritis (6.3%) (P < 0.001 ). Conclusions . The majority of the patients examined had intact cag -PAI. IS605 was present in 15.2% and was higher in H. pylori isolated from patients with gastric carcinoma than in those with peptic ulcer.